2017
DOI: 10.1055/s-0037-1608861
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Plexus Block and Neurolysis in the Management of Chronic Upper Abdominal Pain

Abstract: Chronic upper abdominal pain occurs as a complication of various malignant and benign diseases including pancreatic cancer and chronic pancreatitis, and when present may contribute to lower quality of life and higher mortality. Though various pain management strategies are available as part of a multimodal approach, they are often incompletely effective and accompanied by side effects. Pain originating in upper abdominal viscera is transmitted through the celiac plexus, which is an autonomic plexus located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(123 citation statements)
references
References 84 publications
0
105
1
3
Order By: Relevance
“…Once other causes have been ruled out, the diagnosis can be confirmed with imaging including duplex ultrasound, CT angiography, and magnetic resonance angiography revealing compression or stenosis of the celiac artery 6,8. Percutaneous diagnostic celiac ganglion blockade, in which lidocaine is injected into splanchnic nerves feeding into the celiac plexus, can also be performed by general surgery or IR to predict symptomatic improvement with surgical intervention 1012…”
Section: Discussionmentioning
confidence: 99%
“…Once other causes have been ruled out, the diagnosis can be confirmed with imaging including duplex ultrasound, CT angiography, and magnetic resonance angiography revealing compression or stenosis of the celiac artery 6,8. Percutaneous diagnostic celiac ganglion blockade, in which lidocaine is injected into splanchnic nerves feeding into the celiac plexus, can also be performed by general surgery or IR to predict symptomatic improvement with surgical intervention 1012…”
Section: Discussionmentioning
confidence: 99%
“…The measurements were performed on thin-P a g e / S a y f a | 505 section CT images by simulating a transaortic CPB at the level of the L1 vertebral body (Figure 2.a). As described in the literature, a distance of seven cm from the midline was marked in the left lumbar region by the classical transaortic CPB technique [12,16]. The main line was drawn between the defined point and the celiac plexus region, passing through the aorta.…”
Section: Methodsmentioning
confidence: 99%
“…Neurolytic celiac plexus block (NCPB) of afferent nociceptive fibers as a means to relieve visceral cancerrelated pain using ethanol has been reported to be effective in 74% of patients. CPB can also result in reduced need for opiate analgesics (27,(75)(76)(77)(78)(79). However, this method has some undesirable side effects such as induction of back pain and orthostatic hypertension (75,76).…”
Section: Current Clinical Pain Managementmentioning
confidence: 99%
“…Often called the "silent killer", pancreatic cancer shows few to no symptoms in the early stages. When symptoms, specifically pain, are perceived by the patient they are vague and nonspecific often leading to late diagnosis and poor prognosis due to metastasis to surrounding organs (27)(28)(29)(30). Studies have shown that the majority of pancreatic cancer patients, around 75%, present with pain at the time of diagnosis although pain intensity varies depending on the site of distribution in the pancreas, anatomy and the presence of metastatic lesions or local invasion (28)(29)(30)(31)(32).…”
mentioning
confidence: 99%